2007
DOI: 10.1261/rna.795508
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a tRNA decoding the rare AUA codon in Haloarcula marismortui

Abstract: Annotation of the complete genome of the extreme halophilic archaeon Haloarcula marismortui does not include a tRNA for translation of AUA, the rare codon for isoleucine. This is a situation typical for most archaeal genomes sequenced to date. Based on computational analysis, it has been proposed recently that a single intron-containing tRNA gene produces two very similar but functionally different tRNAs by means of alternative splicing; a UGG-decoding tRNA Instead, we have shown that a tRNA, currently annotat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Aminoacyl∼tRNA_12 is almost completely deacylated within 15 min, whereas deacylation of aminoacyl∼tRNA_34 is incomplete even after 120 min. The half-lives of deacylation of aminoacyl∼tRNA_12 is ∼5 min which is the same as that of Met∼ ; whereas that of aminoacyl∼tRNA_34 is ∼35 min, which is the same as that of [11]. These data, in combination with in vitro re-aminoacylation using purified recombinant H. marismortui MetRS and isoleucyltRNA synthetase (IleRS) , show that tRNA_12 is the elongator methionine , and that tRNA_34 is the minor tRNA Ile (renamed , X representing an unknown modified base).…”
Section: Identification Of the Aua-reading Minor Isoleucine Trna In Amentioning
confidence: 77%
See 2 more Smart Citations
“…Aminoacyl∼tRNA_12 is almost completely deacylated within 15 min, whereas deacylation of aminoacyl∼tRNA_34 is incomplete even after 120 min. The half-lives of deacylation of aminoacyl∼tRNA_12 is ∼5 min which is the same as that of Met∼ ; whereas that of aminoacyl∼tRNA_34 is ∼35 min, which is the same as that of [11]. These data, in combination with in vitro re-aminoacylation using purified recombinant H. marismortui MetRS and isoleucyltRNA synthetase (IleRS) , show that tRNA_12 is the elongator methionine , and that tRNA_34 is the minor tRNA Ile (renamed , X representing an unknown modified base).…”
Section: Identification Of the Aua-reading Minor Isoleucine Trna In Amentioning
confidence: 77%
“…One hypothesis stated that the AUA-reading isoleucine tRNA is derived through alternative splicing of a transcript to produce both a tryptophan tRNA and the isoleucine tRNA [51]. However, using acid urea PAGE, we have shown that the minor AUA-decoding isoleucine tRNA in H. marismortui and other archaeal species is derived from a CAU anticodon-containing tRNA, currently annotated as methionine tRNA, in which C34 in the anticodon is post-transcriptionally modified ( Figure 6A) [11]. In addition, we show that the post-transcriptional modification of C at position 34 in the anticodon of this tRNA, responsible for the switch in amino acid and decoding specificity, is different from those present at position 34 of isoleucine tRNA species in eubacteria and in eukaryotes [52,53].…”
Section: Identification Of the Aua-reading Minor Isoleucine Trna In Amentioning
confidence: 84%
See 1 more Smart Citation
“…The presence of a modified C (C*) with an unknown structure was first reported in Haloferax volcanii tRNA Ile , 14 and was also found in Haloarcula marismortui tRNA Ile . 15 Several analytical methods were used to determine the atomic composition and chemical structure of C* isolated from H. marismortui (Euryarchaeota) and Sulfolobus tokodaii (Crenarchaeota), which results in its identification as 2-agmatinylcytidine (agm 2 ( Fig. 1AB).…”
Section: Aua Decoding By Modified Bases In 3 Domains Of Lifementioning
confidence: 99%
“…We performed a metabolic labeling experiment to test for the incorporation of [ 13 C, 15 N]-labeled agmatine into agm 2 C of tRNA Ile in S. tokodaii and M. acetivorans, and found that agmatine supplied in the medium was efficiently incorporated and used as a substrate for agm 2 C formation. 16 Agmatine is produced from arginine (Arg) via decarboxylation.…”
Section: Biogenesis Of 2-agmatinylcytidinementioning
confidence: 99%